Oral fibrinolytic agent in hyper-coagulopathy in severe COVID – 19 ARDS Patients: two case reports - Dimas Rio Balti; Liem Audi Natalino; Armyta Galuh; Ryan Enast Intan (Journal of the Pakistan Medical Association, 2024)
The use of oral fibrinolytic agent (DLBS1033) has been proven for adjuvant treatment in venous thromboembolism, however until now there is no published report about its uses and effectiveness as an addition to the standard therapy of severe COVID-19 cases and hypercoagulopathy. We present two cases of severe confirmed COVID-19 from PCR tests, seen at Ngimbang Hospital, Lamongan, East Java in October and November, 2020. The first patient was a 51-year-old male who presented to ER with fever, dyspnoea, cough, and oxygen desaturation (SpO2 room air 87%), with comorbids of pulmonary hypertension (PH), atrial fibrillation, heart failure secondary to corpulmonale, and hypercoagulopathy. The second patient was a 56-yearold female who presented with fever, dyspnoea, and oxygen desaturation (Sp02 room air 88%), with comorbid ARDS, hypertension, hyperglycaemia, hypercoagulopathy, heart failure, and CAD. Both of the patients were treated with standard treatment therapy for severe COVID-19 and comorbid therapy, and DLBS1033 in addition to fondaparinux due to limited hospital resources. Both patients showed good clinical outcomes after the course of treatment and had no adverse effects. Conclusions: Our two case reports were the first that showed good clinical outcome and safety of DLBS1033 treatment in addition to fondaparinux for hypercoagulopathy therapy. Keywords: Fondaparinux, Fibrinolytic, COVID-19, Dyspnoea, Atrial Fibrillation, Polymerase Chain Reaction, Hyperglycaemia, Thromboembolism, Respiratory Distress